2018
DOI: 10.5194/aab-61-191-2018
|View full text |Cite
|
Sign up to set email alerts
|

Age-related changes in testicular parameters and their relationship to thyroid hormones and testosterone in male Murrah buffaloes

Abstract: Abstract. The present study aims to investigate the age-related changes in testicular parameters and their association with plasma triiodothyronine (T 3 ), thyroxine (T 4 ), and testosterone in male Murrah buffaloes. Testicular measurements and single blood samples were collected from male Murrah buffaloes (n = 103) aged between 6 months and 8 years. The correlation coefficients of average testicular length (ATL), paired testis width (PTW), and scrotal circumference (SC) in relation to age were 0.88, 0.91, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 28 publications
3
1
0
Order By: Relevance
“…Unlike other traits, change in SNL after 12 months of age was negligible. Like present observation, similar positive correlation of among testicular parameters and with age had been reported in Holstein Friesian (Coulter et al, 1975;Coulter & Foote, 1977), Holstein Friesian X Sahiwal crossbred bulls (Mandal et al, 2004), Sahiwal (Ahmad et al, 2011) and Murrah buffalo (Jadhav et al, 2018) males.…”
Section: Discussionsupporting
confidence: 91%
“…Unlike other traits, change in SNL after 12 months of age was negligible. Like present observation, similar positive correlation of among testicular parameters and with age had been reported in Holstein Friesian (Coulter et al, 1975;Coulter & Foote, 1977), Holstein Friesian X Sahiwal crossbred bulls (Mandal et al, 2004), Sahiwal (Ahmad et al, 2011) and Murrah buffalo (Jadhav et al, 2018) males.…”
Section: Discussionsupporting
confidence: 91%
“…With respect to hormones, the findings of testosterone levels agreed with earlier studie in adult buffalo bulls, with values ranging from 0.2 to 2.7 ng/ml with peripheral testosterone concentrations were lower in younger bulls (Gunarajasingam et al, 1985). Likewise, study in cattle (Kawate et al, 2011) and buffalo (Jadhav et al, 2018) males showed that plasma thyroxine and testosterone increased significantly with age. In cattle and buffalo, increase in serum testosterone between with age, followed by testicular and body growth is corroborated in this study considering the synergistic action of these hormones towards growth (Kastelic et al, 2013;Sakase et al, 2018;Ipsa et al, 2019).…”
Section: Discussionsupporting
confidence: 87%
“…Similarly in Andalusian stallions, serum IGF-1 concentrations determined in different sex and Age groups (Munoz et al, 2011) were in agreement with our findings. From this study, it can be evident tthat scrotal circumference in Bos taurus, Bos indicus and Bubalus bubalis varied with body weight and age and the inter-relationship of the study parameters (body weight, BCS, scrotal circumference, testosterone and growth hormone and IGF-1) agrees with reports in cattle and buffalo (Lee et al, 2005;Torrentera et al, 2009;Singh et al, 2010;Brito et al, 2012;Byrne et al, 2018;Jadhav et al, 2018). These factors inter-play for the onset of reproductive functions and periodic observation of these parameters may act as cue as well intervention yardsticks for enhancing the puberty and sexual maturity in male buffalo.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation